DECISION UNIT SELECTION IN INCREMENTAL SOIL INVESTIGATION OF MULTIPLE POTENTIAL SOURCES AND STATISTICAL TREATMENT OF DIOXIN AND FURAN RESULTS - de Sá Rego, Paulo (Águas Subterrâneas, 2019)
To evaluate contamination from 3 potential sources with diferent conceptual depositional pathways, CH2M performed a Soil Investigation using Incremental Sampling Methodology (ITRM, 2012). Areas where drums and waste were stored above ground on permeable surfaces were identified as potential sources via spills or leakage, and 4 Decision Units (DU) of restricted area (<5,000 m^2) and high sampling density (approx. 4m/pt.). A former waste incinerator was identified as potential source of dioxins and furans via atmospheric deposition, defining a 5th DU. Within this area, a third potential source was identified as a storage for Ascarel-containing transformers, and a smaller DU with higher sampling density was subset into the Dioxin sampling area to ascertain the presence of PCB´s via a spillage/leakage scenario.